THE INFLUENCE OF CORPORATE GOVERNANCE PRACTICE TOWARDS CREDIT AND BOND YIELDS - Rinaningsih Rinaningsih (Faculty of Economics and Business, Universitas Gadjah Mada, 2009)
The purpose of this study is to investigate whether there is a relationship between corporate governance practices and credit risk and bond yields. This study takes samplefrom companies that published bonds in 2006.First, we investigate the relationship between corporate governance practices and credit risk. Credit risk (default risk) can be measured by bond ratings (Billings, 1999).Using ordered probit regressions, we find evidence that the quality of transparency and financial information disclosure that proxied by big-4 auditors and audit committee havesignificant influence on bond ratings, but the relationship between block holders and institutional ownership is not significant on bond ratings. Second, we investigate the relationship between corporate governance practice and bond yields. Using multiple regressions, we find that corporate governance practices is not significant on bond yields. Then we put bond ratings in the equation, we find that bond ratings give incremental effect to the evidence. This evidence is consistent to Bradley et.al, (2007), that bond ratings are the prominent determinant for bond yields. Together with the bond ratings, the corporate governance practices (block holders, institutional ownership, big-4 auditors) have significant influence on bond yields.Keywords: bond ratings, bond yields, corporate governance, credit risk, default risk